Comparative Analysis of the Mitochondrial Genome of Galatheanthemum sp. MT-2020 (Actiniaria Galatheanthemidae) From a Depth of 9,462 m at the Mariana Trench - Shi, Mengke; Qi, Li; He, Li-Sheng (Frontiers in Genetics, 2022)
The hadal zone, represents the deepest marine habitat on earth (6,000-11,000 m), is a harsh environment mainly characterized by extremely high hydrostatic pressure, and believed to have a high degree of endemism in this habitat. Sea anemone family Galatheanthemidae is known as deep-sea species and comprises two valid species exclusively from hadal, but no more information about them is available up to now. In this study, a sea anemone was collected from 9,462 m depth in the Mariana Trench, defined as Galatheanthemum sp. MT-2020 (Actiniaria Galatheanthemidae). The mitochondrial genome of Galatheanthemum sp. MT-2020 was circular with 16,633 bp in length and contained two ribosomal RNA genes, 13 protein-coding genes, and two transfer RNA genes. Though the gene order of Galatheanthemum sp. MT-2020 was identical to that of the majority of species in the order Actiniaria, value of AT-skew was the lowest in the whole mitochondrial genome, with positive GC-skew for atp8 gene, while other species had negative values of GC-skew except Antholoba achates. Galatheanthemum sp. MT-2020 was clustered with another abyssal species Paraphelliactis xishaensis in the phylogenetic tree and they diverged in the early Jurassic around 200 Mya from shallow species. The usage ratio of valine, one of the five amino acids with the most barophilic behavior, in the mitochondrial genomes of the two abyssal species was significantly higher than those inhabiting above 3,000 m. And the ω (dN/dS) ratio of them was 2.45-fold that of the shallow species, exhibiting a slower evolutionary rate. Taken together, this study first provided a complete mitogenome of sea anemone from hadal and revealed some characteristics that may be associated with adaptation to extreme environment.